Effects of CYP2B6 Genetic Variants on the Propofol Dose and Response among Jordanian Arabic Patients Undergoing General Anesthesia - Alrabayah, Mustafa; Massad, Islam M.; Imraish, Amer; Jarrar, Yazun; Massad, Faysal; Guzu, Hasan; Abufares, Basil; Al-Oran, Afnan; Alkharabsheh, Malik Mohammad; Haroon, Nour; Ismail, Mohammad Asa'ad; Qaqish, Bara'a; et al. (Current Drug Metabolism, 2022)
Background: Propofol is the most commonly used general anesthetic drug in many countries, including Jordan. However, there is a wide variation in the propofols' dose and response among the patients. Genetic variation in the cytochrome (CYP) 2B6 gene affects propofol metabolism and might affect propofol dose and response. Aims: This study aimed to determine the influence of major genetic alleles of the CYP2B6 gene, CYP2B6*2A, *6A, *3, *4A, and *5A, on the required propofol dose and response among Jordanian Arabic patients attending The University of Jordan Hospital. Methods: A total of 155 patients were administrated propofol. The propofol response was evaluated by monitoring the time to reach the bispectral index of 60 (BIS60) for every patient. The CYP2B6 genetic variants were genotyped by polymerase chain reaction followed by restriction through specific enzymes for CYP2B6 variants. Results: It is found that patients with variant CYP2B6*2A and *4A alleles required significantly (P < 0.05) lower propofol doses, while patients with variant CYP2B6*6A, *3, and *5A alleles required higher propofol doses in comparison with patients carrying the wild CYP2B6 alleles. Patients with variant CYP2B6*2A and *3 alleles needed a significantly (P < 0.05) shorter while patients with variant CYP2B6*5A allele needed longer time of BIS60 than patients with wild CYP2B6*2A, *3, and *5A alleles. Conclusion: It is concluded that CYP2B6 genetic variants affect propofol dose and can explain, at least partly, the inter-individual variation in the propofol response. Further clinical studies with a larger sample size are needed to confirm the findings of this study.
Keywords: propofol